2007
DOI: 10.1158/0008-5472.can-07-2913
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14-3-3𝛉 as an Antigen that Induces a Humoral Response in Lung Cancer

Abstract: We have implemented a strategy to identify tumor antigens that induce a humoral immune response in lung cancer based on the analysis of tumor cell proteins. Chromatographically fractionated protein extracts from three lung cancer cell lines were subjected to Western blotting and hybridization with individual sera to determine serum antibody binding. Two sets of sera were initially investigated. One set consisted of sera from 19 newly diagnosed subjects with lung adenocarcinoma and 19 matched controls. A second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 29 publications
2
54
0
1
Order By: Relevance
“…However, new studies with larger cohorts need to be done across multiple populations before clinical development to show that CIS could be prospectively detected with the use of our five-autoantibody panel. Interestingly, Hanash et al has recently shown that autoantibody-signature cancer diagnosis is possible months before cancer reaches a size that can be picked up by imaging technology (7,50). Such investigations should be done for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, new studies with larger cohorts need to be done across multiple populations before clinical development to show that CIS could be prospectively detected with the use of our five-autoantibody panel. Interestingly, Hanash et al has recently shown that autoantibody-signature cancer diagnosis is possible months before cancer reaches a size that can be picked up by imaging technology (7,50). Such investigations should be done for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been used to identify TAAs in cancer, including natural protein arrays prepared with fractions obtained from two-dimensional LC separations of tumoral samples (29,30) or protein extracts from cancer cells or tissue (9,31) probed by Western blot with patient sera, cancer tissue peptide libraries expressed as cDNA expression libraries for serological screening (serological analysis of recombinant cDNA expression libraries (SEREX)) (22,32), or peptides expressed on the surface of phages in combination with microarrays (17,18,33,34). However, these approaches suffer from several drawbacks.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Major protein depletion, solution isoelectric focusing, and 1D PAGE resulted in 575 and 2,890 protein identifications from plasma and serum, respectively . Identifying the targets of immune reactions to proteins from cancer cells, normal self cells, and bacteria has been greatly facilitated by the use of PAGE followed by immunological probing with patient sera and mass spectrometry (Brichory et al, 2001;Hong et al, 2006;Pereira-Faca et al, 2007;Basagana et al, 2008;Bunk et al, 2008;Desmetz et al, 2008;Fujita et al, 2008;Hamrita et al, 2008;Nagashio et al, 2008;Taylor et al, 2008;Zhong et al, 2008;Kim et al, 2008b;Liu et al, 2008b;Forgber et al, 2009;He et al, 2009;Patwa et al, 2009;Rao et al, 2009;Shimada et al, 2009;Tamesa et al, 2009;Yi et al, 2009). A large number of protein isoforms in serum, or EDTA versus citrated plasma, were detected by fluorescent labeling prior to separation of the intact proteins by charge, hydrophobic character and molecular mass (Misek et al, 2005).…”
Section: E One-dimensional Poly Acrylamide Gel Electrophoresis (1d Pmentioning
confidence: 99%
“…The peak height or integration method may well be applied on numerous MS instruments (Pereira-Faca et al, 2007;von Haehling et al, 2007;Jacot et al, 2008;Bereman, Williams, & Muddiman, 2009;Mas et al, 2009). It will be a good practice to add recovery and internal quantification standards into crude serum prior to a limited number of fractionation steps to control variation (Mirzaei et al, 2009).…”
Section: Targeted and Internally Or Externally Standardized Mass Specmentioning
confidence: 99%